Covalent Functionalization of Black Phosphorus Nanosheets with Dichlorocarbenes for Enhanced Electrocatalytic Hydrogen Evolution Reaction - Kuchkaev, Aidar M.; Kuchkaev, Airat M.; Sukhov, Aleksander V.; Saparina, Svetlana V.; Gnezdilov, Oleg I.; Klimovitskii, Alexander E.; Ziganshina, Sufia A.; Nizameev, Irek R.; Vakhitov, Iskander R.; Dobrynin, Alexey B.; Stoikov, Dmitry I.; Evtugyn, Gennady A.; et al. (Nanomaterials (Basel, Switzerland), 2023)
Two-dimensional black phosphorus (BP) has emerged as a perspective material for various micro- and opto-electronic, energy, catalytic, and biomedical applications. Chemical functionalization of black phosphorus nanosheets (BPNS) is an important pathway for the preparation of materials with improved ambient stability and enhanced physical properties. Currently, the covalent functionalization of BPNS with highly reactive intermediates, such as carbon-free radicals or nitrenes, has been widely implemented to modify the material’s surface. However, it should be noted that this field requires more in-depth research and new developments. Herein, we report for the first time the covalent carbene functionalization of BPNS using dichlorocarbene as a functionalizing agent. The P–C bond formation in the obtained material (BP–CCl2) has been confirmed by Raman, solid-state 31P NMR, IR, and X-ray photoelectron spectroscopy methods. The BP–CCl2 nanosheets exhibit an enhanced electrocatalytic hydrogen evolution reaction (HER) performance with an overpotential of 442 mV at −1 mA cm−2 and a Tafel slope of 120 mV dec−1, outperforming the pristine BPNS.